Implementing Personalized Energy Visualization Service in Home Network System - Watanabe, Yuichi; Nakamura, Masahide; Matsumoto, Shinsuke (2013 14th ACIS International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing, 2013)
Visualizing energy consumption is a useful method that prompts people to perform energy-saving behaviors. Many systems for the energy visualization come onto the market. Since purposes and attitudes to energy saving vary among individuals, it is difficult to satisfy all users by static ready-made visualization. To cope with the problem, this paper presents Personalized Energy Visualization Service (PEVS), which dynamically generates appropriate visualization for individuals based on preferences. PEVS extracts user's requirement with a questionnaire wizard. We design the questionnaire in a goal-oriented fashion, from viewpoints of term, unit and scope. We then consider how to select an appropriate graph from the answer of the questionnaire. An experimental evaluation shows that every subject was able to create a unique personalized visualization easily.